Wayward Utopias: Time in Wilde and Goethe - Moghrabi, Kafi, MR (AUC Knowledge Fountain, 2024)
In this thesis, I study the dialectical relation between the Utopian imagination and a reality perceived in every way as antagonistic to hope. In the first chapter, I present Ernst Bloch’s Utopian vision, as presented in The Principle of Hope, which offers an exposition of the author’s Romantic Marxism. The second chapter engages Oscar Wilde’s only novel, The Picture of Dorian Gray, demonstrating how a life devoted to self-gratification only results in the constant deferral of Utopian longing, and how, undone, Dorian’s demise opens up Utopian possibilities as anticipated by Bloch. Johann Wolfgang von Goethe’s version of the Faust legend composes the substance of the third chapter, where Faust’s paradoxical salvation is discussed in its full implications. Ernst Bloch will be cited to emphasize how Goethe’s Faust, itself a source for all sources, provided the essential model for Bloch’s philosophy of hope. The study closes in claiming that Bloch’s ideas are not obsolete insofar as the clock is still ticking. Art will continue to figure as a way of reading the Utopian function of culture, even in times that no longer seem able to sustain Bloch’s grand vision.